A consumer's guide for probiotics: 10 golden rules for a correct use. Issue 11 (November 2017) - Toscano, Marco; De Grandi, Roberta; Pastorelli, Luca; Vecchi, Maurizio; Drago, Lorenzo
Abstract: Probiotics are used all over the world as their beneficial effects on the human organism have been widely demonstrated. Certain probiotics can down-regulate production of pro-inflammatory cytokines and promote intestinal epithelial barrier functions, increasing an anti-inflammatory response and contributing to the host's overall health. The main mechanisms by which probiotic microorganisms can interact with the host are by modulating the immune system and the epithelial cell functions and interacting with intestinal gut microbiota. To date, hundreds of different microorganisms are used for the formulation of numerous probiotic products; therefore, it is very difficult to choose the best probiotic product for specific or more general needs. Therefore, physicians are getting more and more confused due to the high number of commercial products which are often lacking healthy effects on the host. Therefore, the aim of this paper is to demonstrate the main characteristics that probiotic microorganisms and products should possess to have a positive impact on the host's health. To this purpose, this review suggests "10 golden rules" or "commandments" that clinicians should follow to properly select the optimal probiotic product and avoid misidentifications, mislabelling and " pie in the sky " stories.